Comparison of Properties of Hydroxyapatite Powders Synthesized by Chemical and Biomimetic Techniques - Yoruc, A. B. Hazar; Karakas, A.; Koyun, A.; Yildiz, T. (POLISH ACAD SCIENCES INST PHYSICS, 2012)
Hydroxyapatite [HA; Ca-10(PO4)(6)(OH)(2)] which composes inorganic phase of bones and teeth is one of the biomedical materials for artificial bone, reconstruction of broken or disordered bones, coating of metallic biomedical materials and dental surgery with its great biocompatibility. In this study, HA powders were synthesized from aqueous suspensions containing H3PO4 and Ca(OH)(2) with 1.67 Ca/P ratios (chemical HA, CHA) and second process is carried out in simulated body fluids consisting of (NH4)(2)HPO4 and Ca(NO3)(2)center dot 4H(2)O as biomimetic hydroxyapatite (BHA). Moreover, properties of bovine HA (BoHA) and commercial HA (CoHA) were compared with properties of synthesized HA powders. Chemical structures of synthesized powders have been examined by the Fourier transform infrared technique and X-ray diffraction. The results showed that BHA powders have a pure HA content and no secondary phase, CHA also has monetite phase as secondary phase with HA in its structure. Particle size analysis was carried out with laser particle sizer and zeta-sizer, surface area of powders has been analyzed by the Brunauer-Emmett-Teller technique. Powder morphology is determined using scanning electron microscopy. As a result two different synthesis methods affected properties of HA powders.
Keywords: Physics